The U.S.- Honduras Remittance Corridor : Acting on Opportunities to Increase Financial Inclusion and Foster Development of a Transnational Economy - Endo, Isaku; Hirsch, Sarah; Rogge, Jan; Borowik, Kamil (World Bank, 2012)
This report on the U.S.- Honduras remittance corridor describes the remittance regulatory and market environment, financial inclusion strategies by financial institutions, transnational economic activities, and the impacts of remittances on the Honduran economy. Six areas provide the focus of this report: (i) regulatory reforms for the remittance market are urgent in order to improve clarity in regulations as well as to include money transfer companies in the regulatory framework; (ii) money service businesses will benefit from an examination of state regulation and their subsequent harmonization and coordination; (iii) rural areas need to improve distributive infrastructure to better reap the benefits of the remittance flows; (iv) financial education and awareness for Honduran migrant communities are critical components with the overall remittance flow equation; (v) the regulatory environment of remittance flows would be greatly enhanced through the promotion, inclusion, and expansion of proper identification; and (vi) public policies can be directed to building an environment for diaspora investments in the community and local business developments for exports to Honduran communities abroad.